The Importance Place of Worship as Support Islamic Education in Senior High School - Nariratih Anggraeni; Budi Haryanto (STAI Hubbulwathan Duri, 2022)
This study aims to determine the means of worship supporting Islamic religious education in SMA Muhammadiyah 2 Sidoarjo. The type of research is descriptive qualitative research. The research subjects used a purposive sampling technique: the principal, Islamic Religious Education teacher and six grade X students. Data collection techniques through interviews and documentation. Data analysis techniques include data collection, reduction, presentation, and conclusions. The results of this study indicate that the means of worship at SMA Muhammadiyah 2 Sidoarjo still use the same mosque as the University of Muhammadiyah Sidoarjo. The facilities for worship are quite complete and are used as a place for teaching and learning in Islamic Religious Education subjects such as practice in schools and mentoring activities. Facilities of worship can support Islamic religious education so that it can facilitate students in exploring and developing the potential of faith, so that later they will not only know and understand, but can implement religious knowledge and faith, and can also live side by side with adherents and adherents of other religions. Thus it can be concluded that the application of the role of the mosque as a means of Islamic education can be a barometer in the symbols of Islam, and Ukhuwah Islaminyah, namely the application of the role of mosques in carrying out religious activities and programs inclusively.